Effect of maternal thyroid hormone levels in late pregnancy on risk of singleton low birth weight - Lin, Qing (Progress in Nutrition, 2023)
Aim: To explore the effect of maternal thyroid hormone levels in late pregnancy on the risk of singleton low birth weight (LBW). Methods: A total of 3757 puerperae who gave birth from September 2019 to October 2020 were divided into case group (n=249, 2500 g). The baseline clinical data of puerperae were collected, and the thyroid hormone levels were compared. The factors with differences were incorporated into LASSO-logistic multivariate regression analysis, the associations between clinical data and thyroid hormone levels were analyzed, and the predictive efficiencies of thyroid hormones for the risk of LBW were assessed using receiver operating characteristic (ROC) curves. Results: Case group had lower level of free triiodothyronine (FT3) and higher levels of free thyroxine (FT4) and thyroid-stimulating hormone (TSH) than those of control group (P